KENAKALAN PADA REMAJA ANDIKPAS (ANAK DIDIK LAPAS): PENGARUH KOMUNIKASI ORANG TUA ATAU SELF-ESTEEM? - Ismayanti, Pratiwi; Hastuti, Dwi (Jurnal Ilmu Keluarga dan Konsumen, 2017)
This study aimed to analyze the relationship of parent-adolescent communication, self-esteem, and delinquency of juvenile prisoners. The study was conducted at the juvenile prison in Bandung and involved 63 boys with age 15-18 years old; who were selected using simple random sampling. Juvenile delinquency was measured using the Adoption Self Report Delinquency Scale (ASRDS) questionnaire by Carroll et al. (1996). The self-esteem instrument used a questionnaire adapted from Rosenberg (1965). The parent-adolescent communication instrument used the Parent-Adolescent Communication Scale questionnaire adapted from Barnes and Olson (1982). Data were analyzed by descriptive analysis and Pearson correlation. Pearson correlation analysis found that there was a positive significant relationship between openness dimension of parent-adolescent communication with the self-esteem of juvenile prisoners. A significant negative relationship was found between problem dimension of parent-adolescent communication with the self-esteem of juvenile prisoners. Furthermore, the study also found a significant negative relationship between openness dimension of parent-adolescent communication and self-esteem with delinquency of juvenile prisoners. There was a significant negative relationship between self-esteem with delinquency of juvenile prisoners.